Perancangan Sistem Informasi Pembuatan Surat Visum Et Repertum di Rsud Soreang dengan Menggunakan Microsoft Visual Studio 2010 - Dinky Andrean Anarki; Yuda Syahidin; Erix Gunawan (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Hospitals as health facilities have a very crucial role. In Indonesia, hospitals have the role of being the final reference. Functioning as a place for recovery & health care, the Hospital in this case is able to provide the best service. The best health services must be synchronized in responding to patient needs. The nursing team on duty must also be equipped with good knowledge and procedures regarding hospital management. Hospitals are required to provide quality services that are synchronized in using established standards and can be reached by all circles of society. The purpose of this paper is to produce an information system design for making Visum Et Repertum letters using Microsoft Visual Studio 2010 at RSUD Soreang. The research methodology used is qualitative using a descriptive approach. Data collection techniques were applied using field work practice procedures, interviews, and literature studies. The development research method used is the waterfall model. Microsoft Visual Studio 2010 as programming language and Microsoft Access 2019 as database. Based on the results of the study, there were problems that were found, namely: (1) the making of the Visum Et Repertum letter had used a computerized system using Microsoft Word but, it was still not effective, (2) the absence of a more effective system to facilitate the making of the Visum Et Repertum letter. Information system Making a visa et Repertum to make it easier for officers in the process of making a visa et Repertum accurately and effectively without any errors.